Sources and use of Indonesia’s foreign debt from an Islamic economic perspective based on Siddiqi’s theory - Sumantri, Nur Adnan Tamalia Ali; Andriansyah, Yuli; Nayak, Venkatesha (Journal of Islamic Economics Lariba, 2024)
Introduction Foreign debt has been a significant factor influencing Indonesia's economic growth, both positively and negatively. Despite its role as a critical source of funding, mismanagement has led to dependency and economic challenges. Research on foreign debt from the perspective of Islamic economics remains limited, especially concerning its sources, utilization, and compliance with Islamic principles.Objectives This study aims to analyze the sources and uses of Indonesia’s foreign debt from an Islamic economic perspective, utilizing M. Nejatullah Siddiqi's theory. It also seeks to assess how foreign debt aligns with Islamic principles and its implications for the country's economy.Method A qualitative research methodology was employed, focusing on a literature review of previous studies, policy documents, and secondary data related to Indonesia’s foreign debt from 2009 to 2018.Results The study identifies that Indonesia's foreign debt is sourced through bilateral and multilateral loans and used primarily for infrastructure and public services. However, significant inefficiencies and interest-based practices conflict with Islamic principles, particularly the prohibition of riba (usury). Misallocation of funds and rising debt levels have further exacerbated economic disparities and dependency on external creditors.Implications To reduce dependency on foreign debt and align financial practices with Islamic principles, policy recommendations include optimizing domestic resource management, implementing Sharia-compliant financing models, and improving accountability in public expenditure.Originality/Novelty This study provides a comprehensive analysis of Indonesia's foreign debt within the framework of Islamic economics, offering practical insights for policymakers to ensure sustainable and ethical economic practices while addressing the country’s financial challenges.